Age‐dependent decline of β‐cell function in type 1 diabetes after diagnosis: a multi‐centre longitudinal study. Issue 3 (29th October 2013) - Barker, A.; Lauria, A.; Schloot, N.; Hosszufalusi, N.; Ludvigsson, J.; Mathieu, C.; Mauricio, D.; Nordwall, M.; Van der Schueren, B.; Mandrup‐Poulsen, T.; Scherbaum, W. A.; Weets, I.; et al.
<x xml:space="preserve">Abstract</x> Aims C‐peptide secretion is currently the only available clinical biomarker to measure residual β‐cell function in type 1 diabetes. However, the natural history of C‐peptide decline after diagnosis can vary considerably dependent upon several variables. We investigated the shape of C‐peptide decline over time from type 1 diabetes onset in relation to age at diagnosis, haemoglobin A1c (HbA1c) levels and insulin dose. Methods We analysed data from 3929 type 1 diabetes patients recruited from seven European centres representing all age groups at disease onset (childhood, adolescence and adulthood). The influence of the age at onset on β‐cell function was investigated in a longitudinal analysis at diagnosis and up to 5‐years follow‐up. Results Fasting C‐peptide (FCP) data at diagnosis were available in 3668 patients stratified according to age at diagnosis in four groups (<5 years, n = 344; >5 years < 10 years, n = 668; >10 years < 18 years, n = 991; >18 years, n = 1655). FCP levels were positively correlated with age (p < 0.001); the subsequent decline in FCP over time was log‐linear with a greater decline rate in younger age groups (p < 0.0001). Conclusions This study reveals a positive correlation between age at diagnosis of type 1 diabetes and FCP with a more rapid decline of β‐cell function in the very young patients. These data can inform the design of clinical trials using C‐peptide values as an end‐point for the effect of a given treatment.